2007 3rd International Conference on Recent Advances in Space Technologies 2007
DOI: 10.1109/rast.2007.4284016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DEM Accuracies Generated by Various Methods

Abstract: Presently, various different methods are I. INTRODUCTION being used for Digital Elevation Model (DEM) generation. DEMs can be generated from topographic maps obtained with terrestrial measurements, As known, Digital Elevation Models (DEM) have big Photogrammetric flight data or Remote Sensing importance for surveying and these are used in large variety of technologies. And also a question can be asked that applications and also lots of different engineering disciplines which method is better than others that's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Digital Elevation Model (DEM) is defined as a data set that presents the elevation information and characteristics of the topography in 3 dimensions (Sefercik, 2007). DEMs can be used as a base for many analyzes that require elevation information in the field of earth sciences.…”
Section: Methodsmentioning
confidence: 99%
“…Digital Elevation Model (DEM) is defined as a data set that presents the elevation information and characteristics of the topography in 3 dimensions (Sefercik, 2007). DEMs can be used as a base for many analyzes that require elevation information in the field of earth sciences.…”
Section: Methodsmentioning
confidence: 99%
“…Although several studies confirmed the ±16 m vertical accuracy at 90% confidence level for SRTM DEM, but some other researchers have reported that SRTM has failed to achieve the expected accuracy of ±16 m (Bonnici and Eisner, 2007) or of low accuracy than contour DEM (Sefercik, 2007) or photogrammetric DEM (Bonnici et al, 2013;Li et al, 2013;Nikolakopoulos et al, 2006;Shafique and van der Meijde, 2014;Thomas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DEM data are an essential tool for many applications such as hydrology, climatology, geomorphology and ecology [2][3][4][5][6]. DEMs can be generated using different methodologies that depend on acquisition procedures and techniques, such as satellite-based techniques, field surveying and topographic maps [7][8][9]. Two global DEMs with horizontal resolutions of 90 m and 30 m were freely downloaded for the study area along with the TM (topographic map) to achieve the study goal.…”
Section: Introductionmentioning
confidence: 99%